Dinamika Ketaatan Kepada Ulil Amri: Studi Tafsir Tematik Dan Implikasinya Bagi Kehidupan Bernegara Di Indonesia - nurkholilah, atu siti (Maliki Interdisciplinary Journal, 2026)
This article examines the dynamics of obedience to ulil amri from a Qur’anic perspective using a thematic interpretation approach and analyzes its implications for state life in Indonesia. The study focuses on the interpretation of Surah An-Nisa verses 58–59, which serve as the foundation for leadership, obedience, and justice in Islam. This research employs a qualitative method with a library research approach, using the Qur’an as the primary data source and classical tafsir works as well as relevant journal articles as secondary data. The findings indicate that obedience to ulil amri in Islam is conditional rather than absolute, depending on the conformity of leaders’ policies with principles of justice and the teachings of Allah and His Messenger. Furthermore, criticism of the government is understood as part of amar ma’ruf nahi munkar as long as it is conveyed ethically and constructively. In the Indonesian context, the concept of ulil amri is compatible with the democratic system and constitutional framework, positioning society as both obedient and critical participants in maintaining justice and national stability.